Adaptive Gelatin Microspheres Enhanced Stem Cell Delivery and Integration With Diabetic Wounds to Activate Skin Tissue Regeneration - Shi, Ming; Gao, Yunfen; Lee, Lim; Song, Ting; Zhou, Jianhua; Yan, Ling; Li, Yan (Frontiers in Bioengineering and Biotechnology, 2022)
The delayed and complicated diabetic wound healing raises clinical and social concerns. The application of stem cells along with hydrogels is an attractive therapeutic approach. However, low cell retention and integration hindered the performance. Herein, gelatin microspheres were fabricated for local delivery of adipose-derived stem cells (from rats, rADSCs), and the effect of rADSCs with microspheres on diabetic wound healing was examined. Uniform, well-dispersed microspheres were fabricated using the microfluidic technique. Due to geometry differences, the proteinase degradation rate for microspheres was four times that of the bulk hydrogel. The obtained gelatin microspheres supported cell's adhesion and proliferation and provided a suitable microenvironment for rADSC survival. For in vivo animal tests, rADSCs were labeled with CM-Dil for tracking purposes. Microspheres were well embedded in the regenerated tissue and demonstrated good biocompatibility and an adaptive biodegradation rate. Histological examination revealed rADSC-loaded gelatin microspheres that significantly accelerated wound healing via promoting M2 macrophage polarization, collagen deposition, angiogenesis associated with peripheral nerve recovery, and hair follicle formation. Notably, the relative fluorescence intensity around the hair follicle was 17-fold higher than that of the blank group, indicating rADSC participated in the healing process via exosomes. Taken together, the rADSC-laden gelatin microspheres provided a promising strategy for local stem cell delivery to improve diabetic wound healing.